2017
DOI: 10.3390/ijms18081778
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Computational Studies of the vCCI:vMIP-II Complex

Abstract: Certain viruses have the ability to subvert the mammalian immune response, including interference in the chemokine system. Poxviruses produce the chemokine binding protein vCCI (viral CC chemokine inhibitor; also called 35K), which tightly binds to CC chemokines. To facilitate the study of vCCI, we first provide a protocol to produce folded vCCI from Escherichia coli (E. coli.) It is shown here that vCCI binds with unusually high affinity to viral Macrophage Inflammatory Protein-II (vMIP-II), a chemokine analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…These results qualitatively corroborated the measured binding affinities, but importantly also produced residue-level “maps” of the interprotein interactions which mediate the binding. To give some examples of structural results noted in this study: the chemokine residue R18 is shown to be important in the binding of both vMIP-II and CCL4; vCCI S182 was seen to have a persistent hydrogen bond to C51; and the vCCI I184 (rabbitpox numbering) which earlier studies in mousepox [ 32 ] had suggested caused unfavorable interactions, was instead seen in the MD simulations to interact with I41 and C51 in vMIP-II [ 69 ].…”
Section: Vcci: a CC Chemokine Binding Proteinmentioning
confidence: 92%
See 2 more Smart Citations
“…These results qualitatively corroborated the measured binding affinities, but importantly also produced residue-level “maps” of the interprotein interactions which mediate the binding. To give some examples of structural results noted in this study: the chemokine residue R18 is shown to be important in the binding of both vMIP-II and CCL4; vCCI S182 was seen to have a persistent hydrogen bond to C51; and the vCCI I184 (rabbitpox numbering) which earlier studies in mousepox [ 32 ] had suggested caused unfavorable interactions, was instead seen in the MD simulations to interact with I41 and C51 in vMIP-II [ 69 ].…”
Section: Vcci: a CC Chemokine Binding Proteinmentioning
confidence: 92%
“…Computational molecular modeling can provide a framework to holistically evaluate the contributions of each residue to this binding interaction. Recently we published a combined experimental and computational study of the binding of vCCI to the chemokine CCL4 and the virally produced chemokine analog vMIP-II [ 69 ]. NMR analysis showed an overall similar binding by vCCI to the two proteins, and fluorescence studies found that vCCI:vMIP-II had a higher binding affinity than vCCI binding to an actual mammalian chemokine, CCL4.…”
Section: Vcci: a CC Chemokine Binding Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown significantly increased levels of macrophage-associated chemokine receptor expression in VM, leading to myocardial damage and immune cell infiltration. Therefore, we believe that M2 EVs can be modified with a chemokine receptor antagonist as one target to gather and target the injured site. Viral macrophage inflammatory protein-II (vMIP-II) is a broad-spectrum chemokine receptor antagonist peptide, which can cooperate with M2 EVs to regulate M1 macrophages in the inflammatory microenvironment, downregulate the levels of multiple chemokine receptors, and competitively inhibit multiple chemokine signaling pathways. , Lysosome-associated membrane protein 2b (Lamp2b) is an EV-specific membrane protein and is an important component in the formation of EVs. Therefore, we used DNA recombination technology to fuse the vMIP-II DNA sequence to Lamp2b enriched on the EVs’ surface to form a fusion protein (vMIP-II-Lamp2b).…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to use proteins naturally produced by pathogens to suppress chemokine-mediated inflammation during infection. To this end, Nguyen et al describe their biophysical studies of two poxvirus proteins, one of which broadly inhibits mammalian chemokines while the other inhibits chemokine receptors [ 16 ]. They find that these two proteins bind extremely tightly to each other and propose a structural basis for the high affinity interaction.…”
mentioning
confidence: 99%